2014
DOI: 10.1111/jcpp.12322
|View full text |Cite
|
Sign up to set email alerts
|

The development of a measure of maternal cognitive sensitivity appropriate for use in primary care health settings

Abstract: The maternal CS measure is brief, can be easily trained, and takes 8 min to administer and code, making it potentially useful in primary healthcare settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 35 publications
2
53
0
1
Order By: Relevance
“…Nevertheless, migrant status appeared to be a risk factor, because it was negatively associated with maternal cognitive sensitivity. In keeping with the findings of Prime et al (2015), U.S. immigrant mothers have been shown to report higher levels of parenting stress than native mothers, with stress predicting aggressive behavior in pre-school age children (Mistry et al, 2008). …”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Nevertheless, migrant status appeared to be a risk factor, because it was negatively associated with maternal cognitive sensitivity. In keeping with the findings of Prime et al (2015), U.S. immigrant mothers have been shown to report higher levels of parenting stress than native mothers, with stress predicting aggressive behavior in pre-school age children (Mistry et al, 2008). …”
Section: Introductionsupporting
confidence: 54%
“…A Canadian study by Wade et al (2014) showed that ToM performance at 5 years was predicted by children’s language competence, but not by family income, migrant status or the presence of siblings in the household. Another study by the same research group (Prime et al, 2015) showed that mother’s communicative clarity and mind-reading skills (termed cognitive sensitivity) were positively related to children’s ToM at 5 years, and receptive language and academic achievement at preschool age. This pattern of associations between mothers’ cognitive sensitivity and children’s outcomes was similar in both native and migrant dyads of mothers and children, suggesting that the underlying process was similar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All scales were coded on a seven‐point scale, and a mean of the three scales across the two tasks was computed. Reliability and validity using the larger study sample can be found elsewhere (Meunier et al ., ; Prime et al ., )…”
Section: Methodsmentioning
confidence: 99%
“…Further, parenting behaviour has been demonstrated as a mediator of the relationship between family‐level risk (e.g. socioeconomic disadvantage) and children's cognitive development (Vernon‐Feagans, ), including language (Prime et al, ). To our knowledge, an indirect pathway from parent verbal abilities to child verbal abilities through parenting behaviour has not been examined.…”
Section: A Proposed Model Of Environmental Transmissionmentioning
confidence: 99%